The INKHOUK: notes on “a fight for construction instead of style” (Palíndromo, 2014)
The Inkhouk was, between 1920 and 1924, one of the most significant organi- zational and institutional displays of Rus- sian and Soviet avant-gardes; deeply em- bedded in the establishment of a Modern State of a new kind and in the full core of a revolutionary dynamic, the Inkhouk was able to prove that not only was it possible for artists to collectively uphold a critical and continuous thinking on the pioneering language and cultural break that they were developing in their artistic work and in their creative methods but it also validated that the political revolution and its every day phenomena had changed the social and symbolic significance of the avant-garde work. The Inkhouk was the moment when modernist activism paused to discern itself while still fully involved in the whirlwind of events.
Keywords: modernism; revolution; avant-garde; constructivism; suprematism